Penegakan Hukum dalam Mengadili Anggota Militer yang Melakukan Tindak Pidana Umum dalam Perspektif Kepentingan Militer - Tetty Melina Lubis; Tiarsen Buaton; Arief Fahmi Lubis; Parluhutan Sagala (Lembaga Pengembangan Kinerja Dosen, 2021)
The punishment imposed on TNI soldiers is actually heavier than the punishment that applies in the general court. The punishment imposed on TNI soldiers is not only limited to prison sentences or fines imposed, but sometimes for serious criminal offenders are often sentenced to additional penalties in the form of dishonorable dismissal (PDTH) from military service. The purpose of this study is to show that for legal subjects with military status, the role of superiors who have the right to punish or called the term Ankum is very dominant. For military members involved in criminal acts, two punishments are imposed, namely first, in the form of disciplinary punishments imposed in the form of punishments for postponement of promotion, demotion to dismissal. This research is qualitative that uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research is carried out. The results of this study show that the determination of absolute competence based on the emphasis on the consequences of the losses incurred can be said to be in line with what is stated in Article 3 paragraph (4) letter a of TAP MRP Number VII of 2000 concerning the Role of the Indonesia National Army and the Role of the National Police of the Republic of Indonesia which reads that